Hemidactylus frenatus (Common House Gecko). Diet - Barquero Arroyo, Marco David (2017)
Hemidactylus frenatus is an invasive species in the Americas that has succeeded in establishing populations in Costa Rica (Savage 2002. The Amphibians and Reptiles of Costa Rica: A Herpetofauna between Two Continents, between Two Seas. University of Chicago Press, Chicago, Illinois. 934 pp.). Although of recent arrival (it is thought to have arrived to the country in the 1990s), it is now widespread and the effects on local fauna (Barquero and Hilje 2005. Wilson Bull. 117:204–205) and human health (Jiménez et al. 2015. Vector Borne Zoonotic Dis. 15:550–555) have just started to be unveiled.